Analisis Perkembangan Kurikulum di Pesantren MBS Nurul Amin Alabio - Miftahul Jannah; Hernadi Hernadi; Muhammad Sabirin (Madrasah: Jurnal Pendidikan Madrasah, 2024)
The curriculum has undergone various interpretations and developments in meaning over time. Initially, the curriculum was viewed as a collection of subjects to be taught, but this view evolved into a series of educational experiences aimed at the holistic development of students. Muhammadiyah, as an organization focused on educational development, has developed a model of Islamic boarding school education that integrates general and religious education. MBS Nurul Amin, under the auspices of Muhammadiyah, uses a curriculum prepared by the Muhammadiyah Islamic Boarding School Development Institute (LP3M), which is different from the national curriculum from the Ministry of Education, Culture, Research, and Technology (KEMENDIKBUDRISTIK). The MBS Nurul Amin curriculum emphasizes the use of Arabic and English as well as the learning of specific religious subjects, while the national curriculum is more general. Since 1997, MBS Nurul Amin has implemented a modern education system and more complete facilities, reflecting a change from previous informal learning methods. Various models of Muhammadiyah Islamic boarding school education reflect the adaptation of the curriculum to the needs of the times and local contexts, with the aim of achieving integration between science, life skills, and strong religious values.